ANALYSIS OF METAL CONTENT OF Pb, Cu AND Zn IN WATER AND SEDIMEN FROM COASTAL KUNDUR ISLAND KARIMUN REGENCY OF ,RIAU ARCHIPELAGO PROVINCE - Sumiati Friesledi Nababan; Irvina Nurrachmi; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT                The reseach was conducted on water and sediment in Kundur Island water to find out metal of Pb,Cu and Zn. The research used purposive method with determination of research areas. The sample was taken on March 2018 and analysis on April 2018 inMarine Chemical Laboratory, Faculty of Fisheries and Marine, University of Riau. The results showed that the metal of Pb in water ranged from 0,2996 – 0,4685 mg/l. The content of Cu 0,2997 – 0,8424 mg/l and Zn 0,5428 – 0,9355 mg/l. The metal of Pb in the sediment ranged from 15.5383 - 22.8933 μg/g. Cu 3,5117 - 7,4750 μg/g and Zn 47,4067 – 77,0167 μg/g. Keywords: Metal content of Pb, Cu, and Zn, Water and Sediment, Kundur Island